The consistency of bootstrap and jackknife variance estimators for finite population L-statistics - Čiginas, Andrius (Lietuvos matematikos rinkinys, 2012)
For the linear combinations of order statistics (L-statistics), we present conditions sufficient for the consistency of their finite-population bootstrap variance estimator and the classical jackknife variance estimator.